DANGEROUS GOODS AS A POSSIBLE TOOL OF COMMITTING THE CRIMINAL OFFENCE OF TERRORISM - Uljanov, Sergej; Stanković, Ivica (The Policy of National Security, 2025)
In times of pronounced globalization processes and no less strong multipolar geopolitical tendencies, the structure of global security is undergoing a serious endurance test, which is why the authors direct their research attention towards the growing potential of manifestation forms of terrorist activities. The phenomenon of dangerous goods is a subject of particular interest to the authors, who first define it conceptually in relation to existing theoretical sources and then examine its normative aspects. After establishing a theoretical and normative foundation, the authors establish a connection between the basic phenomenon of their research and the target problem of terrorism within the framework of criminal law. The authors present the essence of this connection through the possible role of dangerous goods as a tool of committing the criminal act of terrorism, thereby indicating the goal of their research, i.e., the criminal law categorization of the phenomenon of dangerous goods. The methodological concept adopted by the authors comprises a descriptive, historical, normative, analytical, and teleological approach. The authors analyze their research subject through four parts in the paper. After defining the concept and types of dangerous goods, their effective phenomenological positioning in the normative sphere of the criminal act of terrorism follows. The formal-legal segment of the paper gives way to the factual challenges of transporting dangerous goods in road traffic, which is a precursor to the final consideration of possible modi operandi of terrorist attacks using dangerous goods as a crime tool. It is precisely this phenomenological complexity and semantic multi-layering of the concept of dangerous goods, along with its normative and factual imprint on the construction of global security in our time, that form the backbone of the idea presented by the authors in this paper.